Eco-safe citral nanoemulsion for Aedes albopictus control: Mechanistic multi-target toxicological evaluation integrating molecular docking - Souvik Bag; Surajit Ghosh; Dibyendu Saha; Antara Mondal; Nimai Chandra Saha; Soumendranath Chatterjee; Paolo Pastorino; Shubhajit Saha (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Impact of coal mines on aquifer vulnerability and groundwater quality: A DRASTIC-based modified approach in the Raniganj Coalfield (Lower Gondwana) in eastern India - Jaya Chatterjee; Subha Roy; Souvik Das; Md Hasanur Jaman; Prakash Mistri; Somasis Sengupta (Journal of Cleaner Production, 2026)

Understanding the complexities of mustard intercropping: Inferences based on land suitability and farmers’ choices in a paddy-dominated cropping system of eastern India - Prakash Mistri; Souvik Das; Md Hasanur Jaman; Subha Roy; Jaya Chatterjee; Somasis Sengupta (Journal of Cleaner Production, 2026)

Are biopesticides really safe? Impacts on gut microbiota and intestinal health in freshwater fish - Shubhajit Saha; Antara Mondal; Souvik Bag; Surajit Ghosh; Ahamadul Hoque Mandal; Nimai Chandra Saha; Soumendranath Chatterjee; Mentor Sopjani; Cristiana Roberta Multisanti; Caterina Faggio (Journal of Contaminant Hydrology, 2026)

A comprehensive overview of cyanogenic glycosides: Toxicology and innovative sensing approaches - Arindam Niyogi; Soumyadeb Bhattacharyya; Souvik Pal; Subhankar Mukherjee; Subrata Sarkar; Koustuv Ghosh; Alokesh Ghosh; Kumaraswamy Jeyaram; Santosh Keisam; Sirshendu Chatterjee; Om Krishan Singh; Samit Kumar Ray (Food Control, 2025)

Biopesticide (Azadirachtin) as a Sustainable Alternative to Conventional Pesticides (Chlorpyrifos and λ-Cyhalothrin) for Mosquito Control in the Dengue Vector, Aedes aegypti: Insights from Physiological, Histopathological and Molecular Docking Analyses - Souvik Bag; Manabendu Barman; Ayan Mondal; Debraj Biswal; Shubhajit Saha; Soumendranath Chatterjee; Sanjib Ray (International Journal of Environmental Research, 2025)

Novel Hall voltage-assisted enhanced ammonia sensing properties of polyaniline/zinc ferrite composite-based sensor - Mainak Swarnakar; Partha Sarathi Mandal; Mohd Ali; Chandra Shekhar Pati Tripathi; Suchandra Mukherjee; Aritra Banerjee; Sanat Kumar Adhikari; Souvik Chatterjee; Manish Pal Chowdhury (Journal of Environmental Chemical Engineering, 2025)

Intelligent consensus-based predictions of early life stage toxicity in fish tested in compliance with OECD Test Guideline 210 - Souvik Pore; Alexia Pelloux; Anders Bergqvist; Mainak Chatterjee; Kunal Roy (Aquatic Toxicology, 2025)

Identifying topographic disequilibrium conditions and their lithological and tectonic implications in a rifted river basin of Eastern India: Insights from DEM-derived longitudinal profiles and their derivatives - Souvik Das; Subha Roy; Jaya Chatterjee; Md Hasanur Jaman; Somasis Sengupta (Journal of Earth System Science, 2025)

Integrating agricultural land suitability and farmers' perception on crop selection in a water-stressed region of eastern India - Md Hasanur Jaman; Subha Roy; Jaya Chatterjee; Souvik Das; Prakash Mistri; Somasis Sengupta (Agricultural Systems, 2025)

Cat out of the bag: Coastal and Gangetic plains outside protected areas require focus for fishing cat conservation in southern West Bengal, India - Samrat Chakraborty; Tanoy Mukherjee; Supratim Dutta; Souvik Barik; Subhendu Mazumdar; Paromit Chatterjee; Goutam Kumar Saha (Journal for Nature Conservation, 2024)

Machine learning-based q-RASAR predictions of the bioconcentration factor of organic molecules estimated following the organisation for economic co-operation and development guideline 305 - Souvik Pore; Alexia Pelloux; Mainak Chatterjee; Arkaprava Banerjee; Kunal Roy (Journal of Hazardous Materials, 2024)

Sub-basin prioritisation from morphometry for erosion management in an undulating rocky terrain: Validating different MCDM techniques with respect to RUSLE in the Chaka River Basin, Eastern India - Md Hasanur Jaman; Souvik Das; Jaya Chatterjee; Subha Roy; Somasis Sengupta (Journal of Earth System Science, 2024)

GIS-based delineation of potential recharge zones of groundwater and its validation with actual recharge in the Nangasai River Basin of Eastern India - Md. Hasanur Jaman; Jaya Chatterjee; Souvik Das; Subha Roy; Somasis Sengupta (Sustainable Water Resources Management, 2024)

Effect of Metanil Yellow on Pre-natal and Post-natal Physiology: A Study on Rat Model - Sayan Haldar; Spandan Basu; Arpan Chatterjee; Akash Ghosh; Shivkumar Netam; Swapnil Pal; Souvik Mukherjee; Saikat Mukherjee; Arindam Bhattacharyya; Avijit Dey (Proceedings of the Zoological Society, 2024)

Crystal growth mediated physicochemical properties enhancement of CoMnO3 perovskite nanomaterials and its efficient degradation of organic dyes and pathogenic bacteria under mechanical stimuli - Indrajit Mondal; Piyali Halder; Anuja Chatterjee; Neelanjana Bag; Souvik Sau; Somen Biswas; Dheeraj Mondal; Biplab Kumar Paul; Pabitra Kumar Paul; Sukhen Das (Journal of Environmental Chemical Engineering, 2024)

Interlinking erosion susceptibility, channel geometry and stream power: a case study of the Mayurakshi River, eastern India - Subha Roy; Souvik Das; Jaya Chatterjee; Md. Hasanur Jaman; Somasis Sengupta (Environment, Development and Sustainability, 2024)

Potential soil organic carbon sequestration vis-a-vis methane emission in lowland rice agroecosystem - Saikat Ranjan Das; Bitish Kumar Nayak; Souvik Dey; Suman Sarkar; Dibyendu Chatterjee; Saurav Saha; Dibyendu Sarkar; Abhijit Pradhan; Sanjoy Saha; Amaresh Kumar Nayak (Environmental Monitoring and Assessment, 2023)

In Vitro Structure–Activity Relationship Study of a Novel Octapeptide Angiotensin-I Converting Enzyme (ACE) Inhibitor from the Freshwater Mussel Lamellidens marginalis - Madhushrita Das; Ankhi Halder; Roshni Chatterjee; Aditi Gangopadhyay; Tanmoy K. Dey; Souvik Roy; Pubali Dhar; Jana Chakrabarti (International Journal of Peptide Research and Therapeutics, 2023)

Monitoring the temporal dimension of soil erosion in Mayurakshi Basin, India: A novel approach integrating RUSLE, Shannon’s entropy and landscape ecological metrics - Subha Roy; Souvik Das; Somasis Sengupta; Sukhendu Mistry; Jaya Chatterjee (Journal of Earth System Science, 2022)

Diversity and seasonal prevalence of starch hydrolysing, phosphate solubilizing and nitrogen-fixing bacterial groups of rooted and un-rooted regions of tropical mangrove sediments of Sundarbans, West Bengal, India - Souvik Bag; Basanta Sarkar; Madhurima Seal; Arnab Chatterjee; Ayan Mondal; Soumendranath Chatterjee (Marine Biology Research, 2022)

Use of response surface methodology for optimization of a shoot regeneration protocol in Basilicum polystachyon - Dipjyoti Chakraborty; Abhijit Bandyopadhyay; Souvik Bandopadhyay; Kajal Gupta; Aditya Chatterjee (In Vitro Cellular & Developmental Biology - Plant, 2010)

Molecular analysis of the rstR and orfU genes of the CTX prophages integrated in the small chromosomes of environmental Vibrio cholerae non‐O1, non‐O139 strains - Tanuja Bhattacharya; Souvik Chatterjee; Diganta Maiti; Rupak K. Bhadra; Yoshifumi Takeda; G. Balakrish Nair; Ranjan K. Nandy (Environmental Microbiology, 2006)
Summary The ctxAB genes encoding cholera toxin, reside in the genome of a filamentous bacteriophage CTXφ. The presence of CTX prophage in non‐epidemic environmental Vibrio cholerae strains is rare. The CTX prophage, the lysogenic form of CTXφ in V. cholerae , is comprised of the ‘RS2’ and the ‘Core’. Analysis of the rstR gene present in the RS2 region of the CTX prophage revealed the presence of new alleles of the prophages in four environmental non‐O1, non‐O139 strains VCE22 (O36), VCE228 (O27), VCE232 (O4) and VCE233 (O27), and the CTX prophages are located in the small chromosomes. Phylogenetic analysis based on the nucleotide sequences of the rstR and orfU (present in the core) genes of these prophages placed them in a single unique cluster, which is distally located compared with that of epidemic V. cholerae O1 strains. Further analysis indicated that the genome of the prophage present in the strain VCE22 is devoid of the ctxAB genes, called pre‐CTX prophage and the strain also possess the toxin‐coregulated pilus protein coding gene tcpA of classical type, another important pathogenicity determining locus of the epidemic V. cholerae strains. Comparative analysis of the nucleotide sequences of the rstR and orfU genes indicated that the pre‐CTX prophage of VCE22 might be the progenitor of new alleles of the CTX prophages present in these environmental strains.